1.-3ax^3+6ax^2y-3axy^22.4a^2-(a^2+1)^2

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/30 06:27:39
1.-3ax^3+6ax^2y-3axy^22.4a^2-(a^2+1)^2
xO[ 0_Ғ؋x N^}5O;;3ip:s/drh1}3N{afFvhRH[AZ״z; D# "K7_PģOhӘm(<y?>RSnBKv|jW e++{TKԥ,0TgSϕm>شxftw?

1.-3ax^3+6ax^2y-3axy^22.4a^2-(a^2+1)^2
1.-3ax^3+6ax^2y-3axy^2
2.4a^2-(a^2+1)^2

1.-3ax^3+6ax^2y-3axy^22.4a^2-(a^2+1)^2
1.-3ax^3+6ax^2y-3axy^2
=-3ax(x^2-2xy+y^2)
=-3ax(x-y)^2
2.4a^2-(a^2+1)^2
=(2a+a^2+1)(2a-a^2-1)
=-(a^2+2a+1)(a^2-2a+1)
=-(a+1)^2(a-1)^2

1.-3ax³+6ax²y-3axy²
=-3ax(x²-2y+y²)
=-3ax(x-y)²
2.4a²-(a²+1)²
=[2a-(a²+1)][2a+(a²+1)]
=[2a-a²-1][2a+a²+1]
=-(a+1)²(a-1)²